THE READABILITY LEVEL OF READING TEXT IN THE ENGLISH TEXTBOOK ENTITLED “PATHWAY TO ENGLISH” USED THE ELEVENTH GRADE STUDENTS OF STATES ISLAMIC SENIOR HIGH SCHOOL IN TANGERANG - TUTI TILAWATI; Mamik Suendarti (Universitas Indraprasta PGRI, 2022)
The readability level of reading text in the English textbook entitled “Pathway to English” used by the eleventh grade students of State Islamic Senior High School in Tangerang. The objective of the research was to know whether the textbook is suitable to the ability of students, to know whether the reading texts are suitable to student and to know the readability level of reading texts in an English textbook entitled “Pathway to English” which is used by the eleven grade students of State Islamic Senior High School in Tangerang. Method of the research was descriptive qualitative method. The data analyzed through document study. The researcher has completed the following steps which she tries to describe, elaborate, and analyze the readability level of the textbook entitled “Pathway to English” a textbook for eleven grade of state Islamic senior high school in Tangerang. From the writer’s analysis, reading texts in English Textbook entitled “Pathway to English” a textbook for eleven grade of state Islamic senior high school in Tangerang which not readable with students for eleven grade of state Islamic senior high school in Tangerang are: from sixteen reading texts, there are six texts that readable with state Islamic senior high school in Tangerang. The reading texts are text 2, 3, 4, 11, 13 and 16. It can be classified Flesch Reading Ease Score 50-59 the description of the style of the text is fairly difficult. There are six texts from sixteen texts or 37.5 % texts at this level is readable with eleventh grade of state Islamic senior high school in Tangerang. Meanwhile, there are ten texts (62.5 %) from sixteen texts that not readable with state Islamic senior high school in Tangerang.